2013
DOI: 10.1155/2013/402364
|View full text |Cite
|
Sign up to set email alerts
|

Antipoliovirus Activity of the Organic Extract ofEupatorium buniifolium: Isolation of Euparin as an Active Compound

Abstract: The antiviral activity of the organic extract (OE) of Eupatorium buniifolium against poliovirus type 1 was determined by in vitro assays with an effective concentration 50 (EC50) of 23.3 ± 3.3 µg/mL. Bioassay-guided fractionation of the OE allowed the isolation of an active principle that was identified by spectroscopic methods (1H- and 13C-NMR, EI-MS, UV, and IR spectroscopy) as the benzofuran euparin. The plaque reduction assay in Vero cells was used to assess the antiviral activity of euparin against poliov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Antibacterial and antiviral activity [ 28 , 29 ] and protective effect on human lymphocytes against chromosomal damage [ 30 ] have been reported for jaceidin. Euparin has shown antipoliovirus activity [ 31 ] and cytotoxic activity against liver carcinoma cells [ 32 ]. This is the first time that the activity against T. cruzi and L. infantum of these compounds has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial and antiviral activity [ 28 , 29 ] and protective effect on human lymphocytes against chromosomal damage [ 30 ] have been reported for jaceidin. Euparin has shown antipoliovirus activity [ 31 ] and cytotoxic activity against liver carcinoma cells [ 32 ]. This is the first time that the activity against T. cruzi and L. infantum of these compounds has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Euparin is an anti-oxidant benzofuran that has been isolated from several species of Asteraceae, and it was the only phenolic compound from the series that showed activity against DENV-2 with selectivity of action. This natural compound has been evaluated for its activity against poliovirus, demonstrating an inhibition in the early stages of the poliovirus replication cycle, from virus adsorption to cells up to the first twenty minutes after infection, probably affecting the penetration and/or the uncoating process [ 25 ]. Moreover, this benzofuran exhibited activity against other RNA viruses such as respiratory syncytial virus (RSV) and pseudorabies virus strain RC/79 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Linolenic acid compounds were found in the Syzygium paniculatum in the myrtaceae family with levels of (4.85%) and had antioxidant activity (Okoh et al 2019). Euparin compounds also exhibit antioxidant and antifungal activities (Jaime et al 2013). Aeruginosine compounds derived from cyanobacteria also have anti-inflammatory activity (Kapuścik et al 2013), benzofuran compounds have antioxidant activity (Miao et al 2019), and benzofuran was also found in Syzygium cumini L. (Ary et al 2021).…”
Section: Discussionmentioning
confidence: 99%